Apply the quotient rule, which is:
dxdg(x)f(x)=g2(x)−f(x)dxdg(x)+g(x)dxdf(x)
f(x)=cos(x) and g(x)=3x+5.
To find dxdf(x):
-
The derivative of cosine is negative sine:
dxdcos(x)=−sin(x)
To find dxdg(x):
-
Differentiate 3x+5 term by term:
-
The derivative of the constant 5 is zero.
-
The derivative of a constant times a function is the constant times the derivative of the function.
-
Apply the power rule: x goes to 1
So, the result is: 3
The result is: 3
Now plug in to the quotient rule:
(3x+5)2−(3x+5)sin(x)−3cos(x)